2007
DOI: 10.1007/s10389-007-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Health risks related to crop farming in Europe

Abstract: Aim The article aims at describing and summarizing specific risk factors and occupational adverse health effects of agriculture related to typical European crops. Subjects and conclusion A systematic literature review applying a standardized electronic literature search strategy (Medline, Toxnet, EMBASE, AGRICOLA, Science Citation Index) was conducted until February 2007. Studies on specific work-related health risks were included as well as comprehensive reviews summarizing specific adverse health effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To reduce the risk of MSD, more information is needed on the risks with different agricultural tasks in different crops (Germany) [245].…”
Section: Developed Countriesmentioning
confidence: 99%
“…To reduce the risk of MSD, more information is needed on the risks with different agricultural tasks in different crops (Germany) [245].…”
Section: Developed Countriesmentioning
confidence: 99%
“…The work environment of farmers is often characterised by a high workload, long working hours, solitary work, heavy physical labor and a poor work-life balance [6,7]. Research has shown that farmers in several countries experience a variety of health problems, often with epidemiological characteristics that differ from other occupations [8][9][10]. Working farmers have been found to be disproportionately affected by occupational injuries [11,12], chronic musculoskeletal problems [13,14], chronic respiratory conditions [15][16][17][18], depression, anxiety and suicide [19][20][21][22][23][24], and a general reduced quality of life in older age [25].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural work has numerous risks [1]. In the United States and Canada, farming continues to be one of the most dangerous occupations [2].…”
Section: Introductionmentioning
confidence: 99%